2019
DOI: 10.1002/naaq.10086
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Different Winter Feeding Regimens on Growth, Survival, and Fatty Acid Composition of Fathead Minnow and Golden Shiners

Abstract: Winter mortality is a common problem for Arkansas baitfish farmers that produce Fathead Minnow (FHM) Pimephales promelas and Golden Shiners (GS) Notemigonus crysoleucas. Winter feeding programs are a potential avenue to improve survival and condition and reduce weight loss of baitfish. Methods of winter feeding vary widely among producers, and currently there are no recognized best management practices. The impacts of different winter feeding regimens on FHM and GS survival, growth, and lipid storage were eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 39 publications
3
6
0
Order By: Relevance
“…This is the first published report on the effects of different feeding regimens on winter growth and FA composition of Coppernose Bluegill. Data from the present study indicated that all feeding regimes evaluated for winter-fed Coppernose Bluegill resulted in weight loss during the culture period, which is in agreement with previous reports on centrarchids and other fish species cultured in Arkansas (Roy et al 2017(Roy et al , 2019a(Roy et al , 2019b. However, unlike those reports, in which a constant low water temperature was maintained throughout the study, the present study was conducted in an outdoor setting with fluctuating ambient water temperatures.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…This is the first published report on the effects of different feeding regimens on winter growth and FA composition of Coppernose Bluegill. Data from the present study indicated that all feeding regimes evaluated for winter-fed Coppernose Bluegill resulted in weight loss during the culture period, which is in agreement with previous reports on centrarchids and other fish species cultured in Arkansas (Roy et al 2017(Roy et al , 2019a(Roy et al , 2019b. However, unlike those reports, in which a constant low water temperature was maintained throughout the study, the present study was conducted in an outdoor setting with fluctuating ambient water temperatures.…”
Section: Discussionsupporting
confidence: 91%
“…Previously, it was postulated that winter mortality in some cultured species of fish might be due to reduced feeding of fish (i.e., a lower amount of feed administered by the producer, a lower feed intake by the fish, or both) and the concomitant adverse changes due to cold, reduced disease resistance and immunity, and changes in essential FAs (Roy et al 2017). With several published reports on winter feeding regimens for various species of sport fish and baitfish (Roy et al 2017(Roy et al , 2019a(Roy et al , 2019b), it appears highly likely that for most fish species investigated, this may not be an accurate hypothesis. Despite the weight loss exhibited by the fish, survival percentages were generally high in those studies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations